Design and synthesis of water-soluble grifolin prodrugs for DNA methyltransferase 1 (DNMT1) down-regulation. Issue 61 (3rd December 2021) - Wang, Liguo; Wu, Yue; Li, Zhenzhen; Lan, Tianlong; Zhao, Xu; Lv, Wenxing; Shi, Feng; Luo, Xiangjian; Rao, Yu; Cao, Ya
Abstract : In this work, a series of prodrugs of grifolin with much improved solubility and stability were designed and synthesis, which potently downregulated DNMT1 and inhibited tumor proliferation in vitro and in vivo . Abstract : DNA methylation and gene silencing play indispensable roles in the epigenetic landscape and gene expression. DNA methyltransferase 1 (DNMT1), a member of the DNMT family, which catalyzes the addition of methyl groups on DNA has been identified to have a close relationship with tumorigenesis. But DNMT1 inhibitors are rare except for the highly toxic nucleoside derivates. Grifolin is a unique natural product which down-regulates DNMT1 and has low toxicity. However, the poor solubility and stability of grifolin limit its application. Herein, we synthesized PEG5-Grifolin as a water-miscible prodrug of grifolin. The half-life of PEG5-Grifolin at 25 °C was considerably extended, revealing excellent stability. Meanwhile, PEG5-Grifolin suppressed tumor growth of by downregulating DNMT1 and reactivating the expression of several tumor suppressor genes in vivo . PEG5-Grifolin might be a promising demethylation agent for DNMT1 associated diseases and benefit much against various types of DNMT1 associated cancer.